Stress Managemen Related to Farmers' Works: Manajemen Stress Akibat Kelelahan Kerja Pada Petani (JURNAL UNEJ, 2023)
The work of a farmer is accompanied by various risk factors, one of which is work stress. Heavy workloads cause work stress for farmers. Farmers who experience work stress will have an impact on their health. Health education about work stress management for farmers is carried out to provide knowledge about managing work stress. Counseling on stress management related to farmers' work is carried out using the lecture method using leaflets, x-banners, and banners. The material delivered to farmers is the Mental Health Media Kit from the Indonesian Ministry of Health. Farmers' work stress management can be done using physical exercise and relaxation techniques, attending stress management workshops, short daily walks, support from farmer groups, and managing work time effectively to have rest time. Health education for farmers regarding work stress management will continue to be carried out to maintain farmers' mental health.